2020
DOI: 10.1098/rsta.2019.0250
|View full text |Cite
|
Sign up to set email alerts
|

Field-induced circulation flow in magnetic fluids

Abstract: In this paper, we present results of a theoretical study of circulation flow in ferrofluids under the action of an alternating inhomogeneous magnetic field. The results show that the field with the amplitude of about 17 kA m −1 and angular frequency 10 s −1 can induce mesoscopic flow with a velocity amplitude of about 0.5 mm s −1 . This mechanism can be use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 2 publications
0
15
0
Order By: Relevance
“…In the beginning, a drop of the nanoparticle suspension is injected in the centre of the channel and a Gaussian concentration profile is assumed at zero time. This study is the continuation of our two previous works [6,7] dealing with a flat channel and covering only short time scales (after setting on the field) when the nanoparticle concentration profile remains unchanged. These first studies demonstrated that efficient recirculatory flows can only be generated in heterogeneous alternating magnetic fields which in their turn induce heterogeneous nanoparticle concentration profiles.…”
Section: Introductionmentioning
confidence: 70%
“…In the beginning, a drop of the nanoparticle suspension is injected in the centre of the channel and a Gaussian concentration profile is assumed at zero time. This study is the continuation of our two previous works [6,7] dealing with a flat channel and covering only short time scales (after setting on the field) when the nanoparticle concentration profile remains unchanged. These first studies demonstrated that efficient recirculatory flows can only be generated in heterogeneous alternating magnetic fields which in their turn induce heterogeneous nanoparticle concentration profiles.…”
Section: Introductionmentioning
confidence: 70%
“…The obtained results open new opportunities for controlling these phenomena with the help of an applied field. The work of Musickhin et al [32] offers a theoretical study of hydrodynamic patterns induced in liquids (blood, for instance) by suspended ferromagnetic nanoparticles under an alternating magnetic field. The patterned flow can be used for intensification of drug delivery in thrombosed blood vessels for the treatment of insults, stenoses and thromboembolism.…”
Section: (A) Pattern Evolution and The Kinetics Of Growthmentioning
confidence: 99%
“…where  is the angular frequency of the alternating magnetic field, t is the time and the spatial parts h(x,z) of the fields can be calculated by using the standard formulas for the fields of the cylindrical solenoids with given values of the current intensity, radius and length. Exact expressions for h(x,z) are provided in our previous work [5]. Below we will use the notation = 2 / for the period of the field oscillation The results of calculations of the local absolute value H(x,z,t) of the total field H=H1 + H2 are illustrated in Fig.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…A theoretical analysis of the circulation flow in a liquid in a flat channel, a few moments after injection of a ferrofluid drop , under the action of a rotating field has been proposed in ref. [5]. The considered ferrofluid was supposed to consist of individual spherical particles with permanent magnetic moments .…”
Section: Introductionmentioning
confidence: 99%